Telaah Buku Ajar Pengajaran Bahasa Arab di PTAIN - Erlina, Erlina (Universitas Islam Negeri Raden Intan Lampung, 2015)
The study of text book or teaching material is aimed at describing the extent of its feasibility or correspondence to the students’ need. Focusing on the objectives of Arabic language learning—ranging from its achieved language proficiency, subject feasibility, situation, context, and its sequences of learning process–this article tries to study the Arabic text book used by students of IAIN Raden Intan Lampung during their matriculation program. The result of this research shows that the used-Arabic text book is feasible as well as matches with the Arabic learning objective